Avaliação antifúngica do óleo essencial de Lippia origanoides Kunth. E eucaliptol sobre Candida spp. Isoladas de pacientes oncológicos - Silva, Daniel Furtado (2024)
Introduction: Oral candidiasis is a manifestation frequently found after radiotherapy treatment of patients with neoplasms in the head and neck region, which can generate an increase in morbidity and mortality due to immunocompromise and dissemination of the fungal infection. The cytotoxicity presented by conventional antifungals and the increase in fungal resistance are also a current concern. Aims: Identify the current epidemiological profile of patients diagnosed with malignant neoplasms anatomically located in the head and neck region, evaluate the antifungal activity and cytotoxicity of the essential oil of L. origanoides Kunth. (OE) and eucalyptol (EUC), on Candida spp. Materials and methods: This study evaluated the sociodemographic, clinical and therapeutic aspects of these oncology patients. Mycological collection was performed from the oral cavity of patients who completed radiotherapy treatment. In vitro experiments were conducted to evaluate the Minimum Inhibitory Concentration (MIC), Minimum Fungicide Concentration (MFC), mechanism of action, and association with standard antifungals. The hemolytic potential in erythrocytes was also evaluated. The data were analyzed using uni and bivariate descriptive and inferential statistics, using the Chi-Square tests and calculating Cramer's V coefficient. To interpret the data, a significance level of 5% (p < 0.05) and a confidence interval of 95% were considered. Results: The findings demonstrated a higher prevalence of neoplasia in men (54.9%), between 60 and 69 years old (35.4%), pheoderma (78%), with incomplete primary education (26.8%). The most prevalent neoplasm was squamous cell carcinoma (SCC) (63.4%), the most affected areas were the brain (32.9%), followed by the tongue (26.8%), the treatment consisted of a combination of surgery, radiotherapy and chemotherapy was the most adopted (46.3%), and the most used radiotherapy dosage ranged between 70 and 79 Gy (43.8%). Among the patients who participated in the mycological collection, 57.1% had low salivary flow, and 14.3% had very low salivary flow. The diagnosis of oral candidiasis was confirmed in 71.4%, with a predominance of Candida tropicalis (43%), in addition to the unprecedented identification of infection at the oral cavity by Candida magnoliae. Strong antimicrobial activity was observed in both EO (MIC between 32 and 512 μg/mL) and EUC (MIC between 64 and 512 μg/mL). The EO and EUC presented fungicidal potential (MFC/MIC < 4) on the isolated strains, with resistance to nystatin (NIS) (MIC between 128 and 512 μg/mL) and amphotericin B (ANF) (MIC between 2 and 8 μg/mL). Candida albicans isolates showed greater sensitivity to EO and EUC. The findings suggest action on the fungal plasma membrane, in addition to the additive effect in the association of EO with ANF (0.625), and EUC with NIS (0.75). The toxicity analysis demonstrated low hemolytic activity of EO and EUC up to 100 μg/mL, with less cytotoxicity on type A erythrocytes. Conclusion: The results of this research demonstrate the relevance of monitoring fungal resistance and also the development of new antimicrobials in promoting the health and survival of cancer patients. Keywords: